IMPLIKASI DOKTRIN QADARIYAH DAN JABARIYAH DALAM PEMBANGUNAN KARAKTER SOSIAL - Havelia Ramadhani; Abdul Mukti; Zaini Dahlan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2022)
In the process of studying Islam through civilization and thought, Islam has rational thoughts that turn into the form of Firqah or schools, namely Qadariyah and Jabariyah. This flow is based on an understanding of human actions that have different opinions that really contradict each other. Qadariyah with human thought has the will and power in realizing actions, while Jabariyah seems forced, meaning that all actions come from God, humans do not have Masyi'ah or Istitha'ah in determining their actions and destiny. Both of these doctrines have implications for the development of social character since 685 M until the modern era. This research was conducted with a Library Research approach